PENINGKATAN PRODUKTIVITAS DAN EKONOMI KELOMPOK BUDIDAYA JAMUR TIRAM PUTIH (Pleurotus ostreatus) MELALUI TEKNOLOGI PENGATUR SUHU DAN KELEMBABAN KUMBUNG BERBASIS INTERNET OF THINGS (IoT) - Sumartan; Jumadi, Oslan; Wahyuddin, Nur Rahmah; Azwar; Syamsidah; Taufiq, Nur Anny Suryaningsih (Jurnal Abdi Insani, 2024)
This community service program studies the application of Internet of Things-based kumbung temperature and humidity regulation technology for kumbung in the cultivation of white oyster mushrooms in Tasiwalie Village, Pinrang Regency. The aim is to stimulate oyster mushroom cultivation groups to adopt modern technology to increase productivity and economic demand. This method involves a deep understanding of needs groups and the exploration of effective technology solutions. The results show that this technology drives positive changes in cultivation practices, increasing productivity and economic prosperity. With a focus on sustainability, the application of this technology provides long-term benefits for cultivation groups. The implication is that investment in this technology can be a strategy for developing the white oyster mushroom cultivation sector and make a positive contribution to the local economy.